Exploring the Implementation of Data Protection in A Private Institution: Basis for A Strategic Action Plan - Arlegui, Jeriko Arwel (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the implementation of data protection among Senior High School faculty at NU Fairview and developed a Data Protection Strategic Action Plan to strengthen institutional compliance and information security. Anchored on Protection Motivation Theory (PMT), the study explored faculty perceptions of data threats, efficacy in safeguarding student information, existing data protection practices, and barriers affecting compliance. A convergent parallel mixed-methods design was employed, integrating quantitative and qualitative data collected from 45 full-time faculty members through a researcher-made Protection Motivation Appraisal Survey and a semi-structured interview guide. Forty-four faculty members completed the survey, while eight representatives participated in a Focus Group Discussion. Quantitative data were analyzed using descriptive statistics, while qualitative data underwent deductive thematic analysis, followed by data integration through a Joint Display Method. The findings revealed that faculty members demonstrated high awareness of data protection risks and consistently practiced physical and digital safeguards, including data minimization, access control, secure communication, and responsible document handling. However, compliance efforts were constrained by infrastructure limitations, inadequate cloud and physical storage facilities, operational burdens, knowledge gaps, and insufficient policy dissemination. Faculty reported confidence in routine data protection practices but showed lower confidence in technical competencies and formal reporting procedures. The convergence of quantitative and qualitative findings further revealed that many compliance behaviors relied on self-developed workarounds rather than structured institutional support. The study concluded that while faculty possess strong protection motivation, institutional barriers hinder consistent and sustainable compliance. Consequently, the study recommends implementing a Data Protection Strategic Action Plan focused on infrastructure enhancement, policy operationalization, targeted training, and reduced operational friction. This study supports SDG 4 (Quality Education), SDG 9 (Industry, Innovation and Infrastructure), and SDG 16 (Peace, Justice and Strong Institutions) by promoting secure educational environments, responsible digital governance, and strengthened institutional accountability. Its sustainability contribution lies in enhancing educational, technological, and institutional sustainability through improved data governance, privacy protection, and information security practices.
Keywords: Data Protection Strategic Action Plan; Data Protection Practices; Educational Data Privacy; Information Security; Protection Motivation Theory; Senior High School Faculty